2016
DOI: 10.1186/s12977-016-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 capsid uncoating initiates after the first strand transfer of reverse transcription

Abstract: BackgroundCorrect disassembly of the HIV-1 capsid shell, called uncoating, is increasingly recognised as central for multiple steps during retroviral replication. However, the timing, localisation and mechanism of uncoating are poorly understood and progress in this area is hampered by difficulties in measuring the process. Previous work suggested that uncoating occurs soon after entry of the viral core into the cell, but recent studies report later uncoating, at or in the nucleus. Furthermore, inhibiting reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 41 publications
11
96
0
Order By: Relevance
“…An early report suggested that reverse transcription is required for HIV-1 uncoating in target cells (13). Subsequently, Hulme et al reported that inhibition of reverse transcription can delay uncoating (14); this conclusion was supported by subsequent workers using complementary cellbased assays (15,16). In a more recent study employing a novel fluorescence-based HIV-1 imaging assay, uncoating was observed to accelerate upon the initiation of reverse transcription (17).…”
Section: Importancesupporting
confidence: 54%
“…An early report suggested that reverse transcription is required for HIV-1 uncoating in target cells (13). Subsequently, Hulme et al reported that inhibition of reverse transcription can delay uncoating (14); this conclusion was supported by subsequent workers using complementary cellbased assays (15,16). In a more recent study employing a novel fluorescence-based HIV-1 imaging assay, uncoating was observed to accelerate upon the initiation of reverse transcription (17).…”
Section: Importancesupporting
confidence: 54%
“…2B). In recent years, several groups have discovered that it is possible to modulate "uncoating" of HIV-1 particles either by delaying or blocking reverse transcription, or by introducing certain mutations into the CA protein that forms the conical core (2,23,28,29,53,54). A well-established mechanism to disrupt HIV capsid stability is to exploit the mechanism of TRIM5 restriction that recruits the proteasome to direct capsid disruption (16,44).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging hypothesis to the link between early reverse transcription products and the loss of capsid integrity has been recently backed by a study based on both theoretical and mutational studies. Cosnefroy et al (29) suggested that the first-strand transfer of reverse transcription might play a crucial role in core disassembly. However, another concurrent report that measured the binding of tetrameric CypA to the capsid as a tool to follow CA pointed to no correlation between first-strand transfer and uncoating (27).…”
Section: Inhibiting First-strand Transfer Of Reverse Transcription Bymentioning
confidence: 99%
See 2 more Smart Citations